PEMETAAN SAWAH DI SEUNEUBOK BACEE DENGAN MENGGUNAKA METODE TOPOGRAFI DAN UAV (KEC.BENDAHARA, KAB. ACEH TAMIANG) - Siallagan, Indah Agnesia; Delima Simanjutak, Oktavia; Nadya, Yusri; Yusnawati (Fakultas Teknik, Universitas Samudra, 2024)
This study is an independent study that aims toanalyze and determine the scope of irrigation flow in SeunebokAceh Village, Bendahara District, Aceh Tamiang. The methodused is a descriptive quantitative approach with data collectionthrough questionnaires and interviews with 12 respondentsconsisting of residents and village officials. The results of thestudy indicate that several areas experience limited water supplyduring the dry season, the soil structure of the rice fields inSeuneubok Bacee Village, Aceh Tamiang, does not supportagricultural activities, with differences in the height of the ricefield area and the irrigation channel. Where the rice fields arehigher than the irrigation channel itself. This study concludesthat innovative technology is needed, namelythe hydram pump.